The Multilevel Study on the Impact of High-Performance Human Resource Practices on Employees’ Voice Behavior: A Moderated Mediation Model - Liu, Yuanyuan; Liu, Dongxu; Du, Hui; Liu, Shuzhen; Zhou, Xiaoxue (Frontiers in Psychology, 2022)
Based on the social identity theory, the relationship and influencing mechanism between high-performance human resource practices (HPHRPs) and employees’ voice behavior were explored by constructing a moderated mediation model, and the relationship between the field of human resources and the field of organizational behavior was also established. Through 1,178 paired samples of supervisor-employee survey and multilevel linear model analysis technology, it was found that (1) HPHRPs had a positive impact on employees’ voice behavior; (2) perceived insider status played a mediating role between HPHRPs and voice behavior; (3) voice efficacy played a moderating role between perceived insider status and voice behavior; and (4) voice efficacy played a mediating role in the relationship between “HPHRPs-perceived insider status-voice behavior.”